Vortical structures of different scales in a non-rotating and rotating layer of fluid with localized heating - Sukhanovskii, A.N.; Vasiliev, A.Yu.; Evgrafova, A.V.; Popova, E.N.; Stepanov, R.A.; Teymurasov, A.S.; Pavlinov, A.M. (Perm Federal Research Centre Journal, 2017)
A study of vortical structures of different scales in a rotating and non-rotating layer of fluid with localized heating was carried out. In the heating area near the bottom a layer with unstable stratification is formed. The unstable stratification leads to the formation of secondary flows. In a wide range of governing parameters secondary flows appear as a superposition of radial and transverse rolls. The formation of secondary flows is a periodic process, the frequency increases along with a heating. An intensive cyclonic vortex exists in a short interval of the governing parameters. A decrease of viscosity, an increase of heating or angular velocity lead to asymmetry ofthe vortex and further to its breakdown. It was shown that instability of the vortex is strongly connected with a change of the structure of radial flow.